Center-Pivot-Irrigated Sunflowers Cost-Return Budget in Western Kansas - Dumler, Troy J.; O'Brien, Daniel M.; Olson, Brian L.S.; Martin, Kent L. (My University, 2009)
The cost-return projection estimates the cost of producing center-pivot-irrigated sunflowers in western Kansas.
MF800_2009_12
Keywords: MF800; Economics; Crops; MF